Peran Local Strongman dalam Penyelesaian Konflik Tanah pada Industri Tambak Garam di Desa Weoe, Kecamatan Wewiku Kabupaten Malaka: (Studi Kasus Tambak Garam di Desa Weoe, Kecamatan Wewiku Kabupaten Malaka) - Avelin Gatri Seran; Ananias Riyoan Philip Jacob; Yeftha Yerianto Sabaat (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study examines the role of Local Strongmen (Fukun) in resolving land conflicts within the salt pond industry in Weoe Village, Wewiku District, Malaka Regency. The research aims to identify, describe, and analyze the role of local strongmen in mediating land disputes in salt pond operations, as well as to identify challenges encountered during the resolution process. The primary focus is on the function of local strongmen or traditional leaders in addressing land conflicts in this industry. The study employs a qualitative descriptive approach through field research. Data collection techniques include observation, interviews, and literature review. Data analysis follows a structured process involving data collection, reduction, presentation, and verification leading to conclusion drawing. Findings reveal that local strongmen (Fukun) serve as effective mediators in conflict resolution. Their approach facilitates a settlement process that is simple, efficient, and participatory. However, the study identifies a significant challenge: differing perceptions among stakeholders often hinder the achievement of mutually satisfactory agreements.